2020
DOI: 10.3390/atmos11090980
|View full text |Cite
|
Sign up to set email alerts
|

Unmanned Aerial Vehicle Observations of the Vertical Distribution of Particulate Matter in the Surface Layer of the Taklimakan Desert in China

Abstract: Field observations made with unmanned aerial vehicles of the particulate matter (PM) concentration from the ground to a height of 500 m were conducted at Xiaotang and Tazhong in the Taklimakan Desert (TD), China, from 7 to 15 November 2019. The vertical structures of the PM concentrations were studied. Pulsed lidar observations showed that dust aerosols in the TD can reach heights of 4 km. Within 500 m above the ground, the PM1.0, PM2.5, and PM10 concentrations were <100, <201, and <764 µg∙m−3, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Based on the high thermal conductivity and electrical conductivity of LM-based microfluidic electronics [ 35 ], we explored a sensing concept of thermal-dynamic conversion. Due to the soft and stretching performance of the LM microfluidic circuits, the geometrical shape of LM will change along the deformation of the elastomers, as a result, the resistance of LM circuits changes accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the high thermal conductivity and electrical conductivity of LM-based microfluidic electronics [ 35 ], we explored a sensing concept of thermal-dynamic conversion. Due to the soft and stretching performance of the LM microfluidic circuits, the geometrical shape of LM will change along the deformation of the elastomers, as a result, the resistance of LM circuits changes accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…Huang et al (2010) attempted to improve the accuracy of the simulation analysis of clear-sky surface shortwave radiation using the CERES SSF dataset, and aerosol optical depth (AOD) plays a crucial role in deciding the accuracy of simulation analysis. Jin et al (2011) conducted UAV experiments and found that particles size, concentrations, and daily variations in the concentration of PM were different in the Xiaotang and Tazhong Station. On clean days, the mean concentrations of PM 1.0 , PM 2.5 , and PM 10 were 3.6, 6.9, and 18.9 µg•m −3 in the Xiaotang area and 6.5, 13.2, and 26.8µg•m −3 in the Tazhong area, respectively.…”
Section: Evaluatedmentioning
confidence: 99%
“… Huang et al (2020) attempted to improve the accuracy of the simulation analysis of clear-sky surface shortwave radiation using the CERES SSF dataset, and aerosol optical depth (AOD) plays a crucial role in deciding the accuracy of simulation analysis. Jin et al (2011) conducted UAV experiments and found that particles size, concentrations, and daily variations in the concentration of PM were different in the Xiaotang and Tazhong Station. On clean days, the mean concentrations of PM 1.0 , PM 2.5 , and PM 10 were 3.6, 6.9, and 18.9 µg m −3 in the Xiaotang area and 6.5, 13.2, and 26.8 µg mg m −3 in the Tazhong area, respectively.…”
Section: Introductionmentioning
confidence: 99%